Integrated management to reduce fistula‐related long‐term complications and improve the quality of life after arteriovenous fistula surgery: A retrospective cohort study - Min Ning; Dan Luo; Gang Ye; Ting Zhang; Li Liu; Fumei Peng (Wiley, 2021)
Abstract Aim Proper arteriovenous fistula (AVF) management is crucial to avoid AVF complications and prolong its useful life for maintenance haemodialysis (MHD). Design Retrospective cohort study. Methods Patients on MHD who underwent AVF surgery at the Wuhan Third Hospital between January 2018 and July 2018. Results A total of 144 patients were included, with 56 in the integrated group and 88 in the routine group. There were no differences between the two groups in terms of sex (p = .61), age (p = .62) and type of primary kidney disease (p > .99). At 1 year, the integrated group had significantly fewer fistula‐related complications than the routine group (3.6% versus. 23.9%, p < .001). AVF functional scores were lower in the integrated group compared with the routine group (0.1 ± 0.5 versus. 0.8 ± 0.8, p < .001). The pain scores were lower in the integrated group than in the routine group (1.2 ± 0.4 versus. 1.8 ± 0.9, p < .001).